2015
DOI: 10.1200/jco.2015.33.7_suppl.445
|View full text |Cite
|
Sign up to set email alerts
|

Is RCC truly radioresistant? Local control rates of metastatic renal cell carcinoma (RCC) to the lung using stereotactic radiotherapy (SBRT).

Abstract: 445 Background: The use of radiation therapy (RT) for renal cell carcinoma (RCC) is controversial because RCC has traditionally been considered to be “radioresistant”. Based on this concern, current studies have suggested the need for higher doses with conventional fractionation (CF) or the use of SBRT with RCC. The purpose of this study is to determine the efficacy of these modalities by comparing the radiographic and symptomatic local control (LC) rates in patients with metastatic RCC to the lung. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Similar results were reported by Altoos et al showing SBRT-mediated control of thoracic, abdominal, and soft tissue lesions in RCC, with predictive factors for better local control being BED ≥100 Gy and dose per fraction ≥9 Gy [36]. An analysis of radiographic and symptomatic RT responses in 27 consecutive RCC patients with 37 lung lesions found that rates of radiographic local control with SBRT were much higher than CFRT [37]. To explore the difference between SBRT and CFRT on spine metastases from RCC, a total of 110 patients (34 CFRT; 76 SBRT) were retrospectively analyzed [51].…”
Section: Efficacy Of Sbrt In Patients With Advanced Rccsupporting
confidence: 77%
“…Similar results were reported by Altoos et al showing SBRT-mediated control of thoracic, abdominal, and soft tissue lesions in RCC, with predictive factors for better local control being BED ≥100 Gy and dose per fraction ≥9 Gy [36]. An analysis of radiographic and symptomatic RT responses in 27 consecutive RCC patients with 37 lung lesions found that rates of radiographic local control with SBRT were much higher than CFRT [37]. To explore the difference between SBRT and CFRT on spine metastases from RCC, a total of 110 patients (34 CFRT; 76 SBRT) were retrospectively analyzed [51].…”
Section: Efficacy Of Sbrt In Patients With Advanced Rccsupporting
confidence: 77%
“…However, Deschavanne et al in their meta-analysis indicated that α/β ratio (ratio describing tissue sensitivity to change of fraction dose or dose-rate) used to present biologically effective dose (BED) in linear-quadratic model is relatively low (between 2.6 and 4.2), highlighting that potential benefit can be obtained using higher than conventional fractionation dose [24]. The tendency to use hypofractionation in RCC oligometastatic radiotherapy is currently expressed in the number of ongoing clinical trials investigating the use of SABR with encouraging LC and OS results, but these reports relate to visceral metastatic disease only [18,[25][26][27]. Gay et al presented the only accessible in the literature case report on the treatment for cutaneous mRCC with hypofractionated EBRT [28].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although the NCCN does not currently involve RT as part of the standard of care for RCC [11], it is a topic that will need to be further discussed periodically as technologies advance. Most recent studies have focused on the potential role of RT in treating metastases of RCC to other sites, particularly the bone [38,39]. However, we propose that the role of RT, specifically SABR, should be examined and evaluated by the NCCN for the following: treatment of residual disease in the kidney, treatment of previously inoperable RCC, and adjuvant treatment of disease that is at high risk for local dissemination beyond typical nephrectomy beds [40,41].…”
Section: Current Recommendations and Reviewsmentioning
confidence: 99%